Frequency-Dependent Altered Functional Connections of Default Mode Network in Alzheimer’s Disease - Li, Youjun; Yao, Hongxiang; Lin, Pan; Zheng, Liang; Li, Chenxi; Zhou, Bo; Wang, Pan; Zhang, Zengqiang; Wang, Luning; An, Ningyu; Wang, Jue; Zhang, Xi (Frontiers in Aging Neuroscience, 2017)
Alzheimer’s disease (AD) is a neurodegenerative disorder associated with the progressive dysfunction of cognitive ability. Previous research has indicated that the default mode network (DMN) is closely related to cognition and is impaired in Alzheimer’s disease. Because recent studies have shown that different frequency bands represent specific physiological functions, DMN functional connectivity studies of the different frequency bands based on resting state fMRI (RS-fMRI) data may provide new insight into AD pathophysiology. In this study, we explored the functional connectivity based on well-defined DMN regions of interest (ROIs) from the five frequency bands: slow-5 (0.01-0.027 Hz), slow-4 (0.027-0.073 Hz), slow-3 (0.073-0.198 Hz), slow-2 (0.198-0.25 Hz) and low-frequency oscillations (LFO) (0.01-0.08Hz). We found that the altered functional connectivity patterns are mainly in the frequency band of slow-5 and slow-4 and that the decreased connections are long distance, but some relatively short connections are increased. In addition, the functional connectivity fingerprint of the DMN in AD is frequency dependent and differs between the slow-5 and slow-4 bands. Mini-Mental State Examination (MMSE) scores were significantly correlated with the altered functional connectivity patterns in the slow-5 and slow-4 bands. These results indicate that frequency-dependent functional connectivity changes might provide potential biomarkers for AD pathophysiology.